STUDI LITERATUR: KOLABORASI PEMERINTAH DAN MASYARAKAT DALAM MENINGKATKAN KESIAPSIAGAAN BENCANA BANJIR DI INDONESIA - Syifa Nurfajrillah; Rika Wulan; Resty Milandha; Kustawan Hidayat; Edi Setiawan (LPPM UNSAP, 2026)
This study aims to examine the collaboration between government and community in improving flood disaster preparedness in Indonesia. The method used is a literature review with a descriptive qualitative approach. Data were collected from ten scientific articles published between 2013 and 2024. The articles were obtained through a structured search on Google Scholar using keywords such as government and community collaboration, flood preparedness, community participation in disaster mitigation, early warning system, and flood risk management. The findings reveal that flood preparedness across different regions in Indonesia remains uneven. Several areas face challenges due to limited knowledge, weak early warning systems, and lack of community involvement in planning. On the other hand, other regions demonstrate stronger synergy between authorities and residents. This study concludes that inclusive, continuous, and trust-based collaboration between government and society is essential in building a resilient and adaptive flood preparedness system.